2011
DOI: 10.1016/j.jvs.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes for hostile versus favorable aortic neck anatomy in endovascular aortic aneurysm repair using modular devices

Abstract: Patients with HNA can be treated with EVAR, but with higher rates of early (intraoperative) type I endoleak and intervention. The midterm outcomes are similar to FNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
100
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(115 citation statements)
references
References 29 publications
8
100
1
6
Order By: Relevance
“…A proximal neck diameter > 32 mm (hazard ratio [HR] 2.07, 95% confidence interval [95% CI] 1.46-2.92) and aortic angle > 60 degrees (HR 1.96, CI 95% 1.63-2.37) predicted a subsequent increase in the diameter. 7 Although the image reviews in this retrospective and limited analysis do not reflect the rates usually reported for diameter increase of the aneurysmatic sac (40% versus approximately 10% in a period of three to five years) or the clinical significance of this finding, they represent a good example of the differences in results arising from liberal patient selection.…”
Section: See Page 69mentioning
confidence: 80%
See 4 more Smart Citations
“…A proximal neck diameter > 32 mm (hazard ratio [HR] 2.07, 95% confidence interval [95% CI] 1.46-2.92) and aortic angle > 60 degrees (HR 1.96, CI 95% 1.63-2.37) predicted a subsequent increase in the diameter. 7 Although the image reviews in this retrospective and limited analysis do not reflect the rates usually reported for diameter increase of the aneurysmatic sac (40% versus approximately 10% in a period of three to five years) or the clinical significance of this finding, they represent a good example of the differences in results arising from liberal patient selection.…”
Section: See Page 69mentioning
confidence: 80%
“…The frequency of hostile anatomy in this patient population can be as high as 50% to 60%. 6,7 In this issue of the Revista Brasileira de Cardiologia Invasiva, Metzger et al 8 reported their experience treating a small group of patients with hostile anatomy, defined by the presence of a strong angulation in the proximal aortic neck or in the emergence of the iliac arteries. In the authors' experience, the use of a device whose characteristics were ideal for this situation produced acceptable success and complication rates.…”
Section: See Page 69mentioning
confidence: 99%
See 3 more Smart Citations